Cracks as Efficient Tools to Mitigate Flooding in Gas Diffusion Electrodes Used for the Electrochemical Reduction of Carbon Dioxide. Issue 9 (10th July 2022) - Kong, Ying; Liu, Menglong; Hu, Huifang; Hou, Yuhui; Vesztergom, Soma; Gálvez‐Vázquez, María de Jesus; Zelocualtecatl Montiel, Iván; Kolivoška, Viliam; Broekmann, Peter
Abstract: The advantage of employing gas diffusion electrodes (GDEs) in carbon dioxide reduction electrolyzers is that they allow CO2 to reach the catalyst in gaseous state, enabling current densities that are orders of magnitude larger than what is achievable in standard H‐type cells. The gain in the reaction rate comes, however, at the cost of stability issues related to flooding that occurs when excess electrolyte permeates the micropores of the GDE, effectively blocking the access of CO2 to the catalyst. For electrolyzers operated with alkaline electrolytes, flooding leaves clear traces within the GDE in the form of precipitated potassium (hydrogen)carbonates. By analyzing the amount and distribution of precipitates, and by quantifying potassium salts transported through the GDE during operation (electrolyte perspiration), important information can be gained with regard to the extent and means of flooding. In this work, a novel combination of energy dispersive X‐ray and inductively coupled plasma mass spectrometry based methods is employed to study flooding‐related phenomena in GDEs differing in the abundance of cracks in the microporous layer. It is concluded that cracks play an important role in the electrolyte management of CO2 electrolyzers, and that electrolyte perspiration through cracks is paramount in avoiding flooding‐related performance drops. Abstract : Newly developed approach combining scanning electron microscopy, energy dispersive X‐ray spectroscopy, and inductively coupled plasma‐mass spectrometry is applied to investigate electrolyte flooding in gas diffusion electrodes for the electrochemical reduction of carbon dioxide. It is demonstrated that cracks in the microporous layer serve as efficient pathways for draining excess electrolyte allowing flooding‐related performance losses to be avoided.